Changing of the guard: Structural change and corporate science in the semiconductor industry - Maikel Pellens; Antonio Della Malva (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
This article documents a structural change in the production of science in the U.S. semiconductor industry over almost three decades. We observe a change in scientific productivity over time, where smaller firms publish more articles per dollar in R&D. Moreover, our results show a positive relationship between the value of intangibles and scientific publications, driven by basic research results. These effects are especially strong among Fabless 'design' firms and among firms in the post-PC era of semiconductor manufacturing, in line with a premium for smaller firms which invest in science in times of structural technological change.
urn:nbn:de:bsz:180-madoc-413829
Keywords: O31; O33; 330; corporate science; basic science; firm value; semiconductors